Why are we awake? Algorithmic serendipity and the sociology of sleeplessness - Bo, Boroka; O’Sullivan, Aidan; Bariol, Eva; Kucherenko, Nicole; Behan, Molly (Frontiers in Sociology, 2025)
Algorithmic serendipity is the seemingly chance encounter with exactly the right content, engineered by online recommender systems, linking individuals to one another and to digital remedies. This phenomenon transforms the individual experience of insomnia into a collective experience, creating communities around shared sleeplessness. Using a corpus of YouTube comments, we present a comprehensive theory of how algorithmic mediation may reshape insomnia in late modernity. Insomniacs forgo rest to read and share their experiences with sleeplessness, forging community instead of sleep. In tracing this loop, we show how disclosure practices, peer validation, and platform logic fuse to turn a private symptom into a shared social condition. The result is a paradox: the same digital infrastructures that soothe wakeful nights sustain insomnia. Recognizing this underscores that digital culture must sit at the center of sleep research. Interventions should target not only individuals, but the collective rhythms and norms that animate digital worlds.